Stabilization of Acute High-Grade Acromioclavicular Joint Separation: A Prospective Assessment of the Clavicular Hook Plate Versus the Double Double-Button Suture Procedure. Issue 11 (September 2018) - Stein, Thomas; Müller, Daniel; Blank, Marc; Reinig, Yana; Saier, Tim; Hoffmann, Reinhard; Welsch, Frederic; Schweigkofler, Uwe
Background: The stabilization strategy for acute high-grade acromioclavicular (AC) joint separations with AC-stabilizing clavicular hook plate (cHP) or coracoclavicular (CC)–stabilizing double double-button suture (dDBS) is still under consideration. Hypothesis: The CC-stabilizing dDBS is superior to the cHP according to an AC-specific radiologic assessment and score system. Study Design: Cohort study; Level of evidence, 2. Methods: Seventy-three consecutive patients with acute high-grade AC joint separation were prospectively followed in 2 treatment groups (64.4% randomized, 35.6% patient-selected treatment): open reduction and cHP (cHP group) or arthroscopically assisted dDBS (dDBS group) performed within 14 days of injury. Patients were prospectively analyzed by clinical scores (Taft, Constant score [CS], numeric analog scale for pain) and AC-specific radiographs (AC distance, CC distance [CCD], relative CCD [rCCD; 100 / AC distance × CCD]) at points of examination (preoperative and 6, 12, and 24 months). The minimal clinically important differences (MCIDs) were assessed by the anchor-based method. Results: Twenty-seven of 35 patients (mean age ± SD: 37.7 ± 9.7 years) after cHP implantation and 29 of 38 patients (34.2 ± 9.7 years) after dDBS implantation were continuously followed until the 24-month follow-up. All patients showed significantly increased scores after surgery as compared with preoperative status (all P < .05). As compared with GI, GII had significantly better outcomes at 24 months (Taft: cHP = 9.4 ± 1.7 vs dDBS = 10.9 ± 1.1, P < .05, MCID = 2.9; CS: cHP = 90.2 ± 7.8 vs dDBS = 95.3 ± 4.4, P < .02, MCID = 16.6) and at 24 months for Rockwood IV/V (Taft: cHP = 9.4 ± 1.7 vs dDBS = 11.1 ± 0.8, P < .0005; CS: cHP = 90.1 ± 7.7 vs dDBS = 95.5 ± 3.1, P < .04). Clinically assessed horizontal instability persisted in 18.52% (GI) and 6.89% (GII; P = .24). The rCCD showed equal loss of reduction at 24 months (GII = 130.7% [control = 111%] vs GI = 141.8% [control = 115%], MCID = 11.1%). Conclusion: This prospective study showed significantly superior outcomes in all clinical scores between GII and GI. The subanalysis of the high-grade injury type (Rockwood IV/V) revealed that these patients showed significant benefits from the dDBS procedure in the clinical assessments. The cHP procedure resulted in good to excellent clinical outcome data and displayed an alternative procedure for patients needing less restrictive rehabilitation protocols.